Political control of the economy - Tufte, Edward R., 1942- (Princeton University Press, 1978)
Edward R. Tufte seeks to determine the impact of political life on the national economy of America and other capitalist democracies. The analysis demonstrates how politicians, political parties, and voters decide who gets what, when, and how in the economic arena. A nation's politics, it is argued, shape the most important aspects of economic life: inflation, unemployment, income redistribution, the growth of government, and the extent of central economic control. Both statistical data and case studies (based on interviews and Presidential documents) are brought to bear on four topics. They are: 1) the political manipulation of the economy in election years, 2) the new international electoral-economic cycle, 3) the decisive role of political leaders and parties in shaping macroeconomic outcomes, and 4) the response of the electorate to changing economic conditions. Finally, the book clarifies a central question in political economy: How can national economic policy be conducted in both a democratic and a competent fashion?